The oldest teleosts (Teleosteomorpha): their early taxonomic, phenotypic, and ecological diversification during the Triassic - Gloria Arratia; Hans-Peter Schultze (Fossil Record, 2024)
As the fossil record reveals, neopterygians had a major diversification after the great mass extinction at the Permian-Triassic boundary, including the appearance of the major clade Teleosteomorpha. Detailed studies of new taxa (Pseudopholidoctenus germanicus, Barschichthys ruedersdorfensis, and Ruedersdorfia berlinensis) from the lower Anisian (middle Muschelkalk) of Germany and their comparisons with other Triassic relatives are presented, including new information concerning size, shape, and diet. Two families, Pholidophoridae and Marcopoloichthyidae, made a modest appearance during the Anisian of Europe and Asia almost simultaneously, with Pseudopholidoctenus (and the teleosteomorphs Barschichthys and Ruedersdorfia) from the Germanic Basin, being the oldest stem teleosts (244 Ma), followed shortly by Marcopoloichthys ani from Italy. The early teleostean diversification was fast—already in the late Ladinian three lineages were present: Prohalecitiidae (Europe), Pholidophoridae (Asia, Europe), and Marcopoloichthyidae (Asia, Europe), with ca. 20 species inhabiting the Tethys Ocean during the Middle–Late Triassic. Most Triassic teleosteomorphs were small, ca. 50 mm standard length, and a few as possibly miniature, with torpedo or oblong shapes, and suction feeders—probably a plankton based-diet. These first Triassic radiations were replaced during the early Sinemurian of marine ecosystems of Europe with two major groups: (a) non-monophyletic ‘pholidophoriforms’ and (b) proleptolepids and leptolepids, having an average size (ca. 100 mm SL) longer than Triassic forms, with oblong and fusiform shapes. A fast dispersion from the Tethys to the Paleo-Pacific followed, as demonstrated by the presence of small (ca. 50 mm SL) suction feeder proleptolepids in the early Sinemurian of Chile.